2020
DOI: 10.1186/s12958-019-0559-7
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal ovarian drilling followed by controlled ovarian stimulation from the next day improves ovarian response for the poor responders with polycystic ovary syndrome during IVF treatment: a pilot study

Abstract: Background: Poor response patients with PCOS who are not susceptible to gonadotropin stimulation are more likely to have canceled cycles or poor clinical outcomes during IVF treatment. However, some limitations exist in the present therapies. In this study, we evaluated the effects of using the transvaginal ovarian drilling (TVOD) followed by controlled ovarian stimulation (COS) from the second day of these poor responders. Methods: During IVF, 7 poor responders with PCOS and 28 PCOS patients (14 normal and 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The management of POR in women with PCOS is varied: cancellation of the cycle, switching to intrauterine insemination (if the tubal obstruction is not present), dual stimulation, switching from IVF to IVM as a salvage strategy ( 37 ), or transvaginal ovarian drilling followed by controlled ovarian stimulation from the next day onwards ( 38 ). Our study provides new data that when the expected number of oocytes is more than four, the live birth rate of a fresh transfer is not affected.…”
Section: Discussionmentioning
confidence: 99%
“…The management of POR in women with PCOS is varied: cancellation of the cycle, switching to intrauterine insemination (if the tubal obstruction is not present), dual stimulation, switching from IVF to IVM as a salvage strategy ( 37 ), or transvaginal ovarian drilling followed by controlled ovarian stimulation from the next day onwards ( 38 ). Our study provides new data that when the expected number of oocytes is more than four, the live birth rate of a fresh transfer is not affected.…”
Section: Discussionmentioning
confidence: 99%
“…Increased insulinsensitivity also occurs after LOD probably in close relationship with decreased androgen secretion (9,23). Transvaginal ovarian drilling results after only one day following procedure in decreased testosterone and AMH in serum and follicular fluid in women undergoing controlled ovarian stimulation protocol with GnRH antagonists for IVF (24).…”
Section: Reproductivementioning
confidence: 94%
“…Thus, for preventing OHSS and saving cost, we suggested that patients should be performed IVM as earlier as the patients were undergoing moderate to severe OHSS tendency. Even patients obtained no live birth, the puncture of small follicles can be equal to the treatment of transvaginal ovarian drilling which might bene t the next ovarian stimulation cycle (42).…”
Section: General Characteristics Of Patients Are Displayed In Tablementioning
confidence: 99%